Development of 2D Animation Application Learning to Drive Class D Vehicles on The Driving School Circuit - Sham, Md Azani; Abdul Shukor Ashraf Abd Samad; Hamzah, Usuloudin; Yasak, Zurina (Research and Innovation in Technical and Vocational Education and Training, 2024)
The goal of this project was to create a 2D animation application for teaching class D vehicle driving on the driving school circuit as an extra learning tool for teachers and applicants for driving tests. As a design paradigm with five phases: design, development, implementation, and analysis, the ADDIE model has been chosen. This 2D animated Android app was created by the creators using Adobe Animate and Adobe Illustrator. Three multimedia experts who teach at the Faculty of Technical and Vocational Education and three content experts who teach in driving schools make up the group of chosen specialists. The information was gathered, examined, and given as feedback comments and frequency values. The results of the data analysis demonstrate that all three experts concur on the interaction design, but there is disagreement among them about the interface design and how the multimedia element is presented. This suggests that the developer has to make some improvements in these areas. On the other hand, when it comes to content specialists, everyone agrees on the application’s content design. In conclusion, the Android application’s construction has been successfully tested for functionality.